The PANcreatic Disease ReseArch (PANDoRA) consortium: ten years’ experience of association studies to understand the genetic architecture of pancreatic cancer - Campa, Daniele; Stein, Angelika; Loos, Martin; Katzke, Verena; Brenner, Hermann; Büchler, Markus W.; Hackert, Thilo; Neoptolemos, John P.; Schöttker, Ben; Giese, Nathalia; Kaaks, Rudolf; Holleczek, Bernd; et al. (Critical reviews in oncology, hematology, 2023)
Pancreatic cancer has an incidence that almost matches its mortality. Only a small number of risk factors and 33 susceptibility loci have been identified. Moreover, the relative rarity of pancreatic cancer poses significant hurdles for research aimed at increasing our knowledge of the genetic mechanisms contributing to the disease. Additionally, the inability to adequately power research questions prevents small monocentric studies from being successful. Several consortia have been established to pursue a better understanding of the genetic architecture of pancreatic cancers. The Pancreatic disease research (PANDoRA) consortium is the largest in Europe. PANDoRA is spread across 12 European countries, Brazil and Japan, bringing together 29 basic and clinical research groups. In the last ten years, PANDoRA has contributed to the discovery of 25 susceptibility loci, a feat that will be instrumental in stratifying the population by risk and optimizing preventive strategies.